Utilization of Date Palm Fruits for Making Delicious Biscuits - Singh, R S; Pal, Garima; Bhargava, R; Sharma, B D (Annals of Arid Zone, 2016)
The ripe fruits of date palm (doka or khalal) are used for fresh consumption and processing. Date fruit pulp is used for flavoring the bakery products. In India, limited work has been carried out on post harvest management for proper utilization of date fruits. Keeping this in view, an attempt was made to utilize doka stage fruits for preparation of nutritious biscuits. The small size, astringent in taste, unfit for dry date and pind khajoor these can be utilized to prepare biscuits. The fruits were cut in to pieces, after removing seeds, for drying and grinding to make powder. Biscuits were prepared in bakery by adding date pulp powder in ratio of 10, 20 and 30% in wheat flour and other ingredients like sugar, milk and ghee. In control biscuits date pulp powder was not mixed. The study indicated that date biscuits prepared by adding of 10 or 20% pulp powder were suitable on organoleptic score basis for taste, flavor, appearance and acceptability as well as rich in sugars and protein from nutrition point of view. Key words: Date palm, Phoenix dactylifera, doka stage fruits, value addition, biscuits.